Preparation and toolkit learning - Mark Voorneveld (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
A product set of pure strategies is a prep set (prep is short for preparation) if it contains at least one best reply to any consistent belief that a player may have about the strategic behavior of his opponents. Minimal prep sets are shown to exists in a class of strategic games satisfying minor topological conditions. The concept of minimal prep sets is compared with (pure and mixed) Nash equilibria, minimal curb sets, and rationalizability. Additional dynamic motivation for the concept is provided by a model of adaptive play that is shown to settle down in minimal prep sets.
Keywords: C72; D83; 330; noncooperative games; inertia; status quo bias; adaptive play; procedural rationality; Spieltheorie; Adaptive Erwartung